Outcomes of chronic total occlusion percutaneous coronary intervention in patients with reduced left ventricular ejection fraction. Issue 4 (23rd January 2022) - Simsek, Bahadir; Kostantinis, Spyridon; Karacsonyi, Judit; Alaswad, Khaldoon; Karmpaliotis, Dimitri; Masoumi, Amirali; Jaffer, Farouc A.; Doshi, Darshan; Khatri, Jaikirshan; Poommipanit, Paul; Gorgulu, Sevket; Goktekin, Omer; et al.
Abstract: Background: The relationship between left ventricular ejection fraction (LVEF) and the success and safety of coronary chronic total occlusion (CTO) percutaneous coronary intervention (PCI) has received limited study. Methods: We examined the clinical characteristics and outcomes of CTO PCI in the Prospective Global Registry for the Study of CTO Intervention (PROGRESS‐CTO) after stratifying patients by LVEF (≤35%, 36%–49%, and ≥50%). Results: A total of 7827 CTO PCI procedures with LVEF data were included. Mean age was 64 ± 10 years, 81% were men, 43% had diabetes mellitus, 61% had prior PCI, 45% had prior myocardial infarction, and 29% had prior coronary artery bypass graft surgery. Technical success was similar in the three LVEF strata: 85%, 86%, and 87%, p = 0.391 for LVEF ≤35%, 36%–49%, and ≥50%, respectively. In‐hospital mortality was higher in lower LVEF patients (1.1%, 0.4%, and 0.3%, respectively, p = 0.001). In‐hospital major adverse cardiovascular events (MACE) were numerically higher in lower EF patients (2.7%, 2.1%, and 1.9%, p = 0.271). At a median follow‐up of 2 months (interquartile range: 19‐350 days), patients with lower LVEF continued to have higher mortality (4.9%, 3.2%, and 1.4%, p < 0.001) while the MACE rates were similar (9.3%, 9.6%, and 7.4%, p = 0.172). Conclusion: CTO PCI can be performed with high technical success in patients with reduced LVEF but is associated with higher in‐hospital and post‐discharge mortality.